(untitled) (Clinics, 2014)
OBJECTIVE: It has been shown that SOCS-1 plays an important role in the proper control of cytokine/growth factor responses and acts as a tumor suppressor in acute myeloid leukemias. Therefore, the objective of the present study was to evaluate the in vitro effect of treatment with Nutlin-3, a small molecule inhibitor of the MDM2/p53 interaction, on the expression of the suppressor of cytokine signaling 1 in primary acute myeloid leukemia cells and in myeloid cell lines with differential p53 status. METHOD: The expression of the suppressor of cytokine signaling 1 was quantitatively analyzed by real-time PCR in myeloid p53wild-type (OCI and MOLM) and p53null HL-60, leukemic cell lines, in patient-derived acute myeloid leukemia blasts, and in primary normal cell types, such as macrophages, endothelial cells, and bone marrow mesenchymal stem cells. The p53-dependence of the suppressor of cytokine signaling 1 upregulation that is induced by Nutlin-3 was analyzed in experiments performed using siRNA for p53, while the functional upregulation of the suppressor of cytokine signaling 1 was analyzed by assessing the levels of phosphorylated STAT-3. RESULTS: Nutlin-3 significantly upregulated the transcription of the suppressor of cytokine signaling 1 in p53wild-type OCI and MOLM but not in p53deleted p53null HL60, myeloid leukemic cell lines, as well as in primary acute myeloid leukemia blasts. Conversely, and somewhat unexpectedly, Nutlin-3 did not modulate the suppressor of cytokine signaling 1 expression in primary normal macrophages, endothelial cells, and bone marrow mesenchymal stem cells. The p53-dependent upregulation of the suppressor of cytokine signaling 1 by Nutlin-3 was associated with the downregulation of phosphorylated STAT-3, a major molecular target of the suppressor of cytokine signaling 1. CONCLUSION: Overall, our data suggest a potential role for the suppressor of cytokine signaling 1 as a therapeutic target of Nutlin-3 in p53 wild-type acute myeloid leukemias.